Effect of Patient Counselling Based Intervention in Hypertensive Outpatients - Shah, Parshwa; Patel, Het; Oza, Kanjav; Shah, Nupoor; Despande, Shrikalp; Patel, Chintan (Journal of Pharmacy Practice and Community Medicine)
Objectives: To evaluate the effectiveness of patient counselling based intervention on blood pressure, medication adherence and knowledge in hypertensive patients. Materials and Methods: A prospective, multi-centric, randomized controlled interventional study conducted for period of 4 months at 2 outpatient’s clinics in Gandhinagar city, Gujarat. Enrolled patients were randomized into 2 groups (Intervention and Control) using simple randomization technique with allocation ratio of 1:1. Morisky Medication Adherence Scale (MMAS-4), self-designed Case Record Form (CRF) and self-designed knowledge questionnaire were utilised for data collection. Each patient was followed for 2 months with a total of 4 follow-ups each 15 days apart. Patient counselling and education was provided using patient information leaflet (PIL) in interventional group. Results: A total of 105 patients were randomized into two groups. The result revealed significant reduction i.e. 10 mmHg in systolic blood pressure (SBP) and 5.78 mmHg in diastolic blood pressure (DBP) in interventional group (p< 0.0001) from baseline to final visit whereas no significant difference was seen in control group. Interventional group showed significant change in medication adherence (p = 0.0011) as well as in hypertension related knowledge (p<0.0001) wherein control group showed no significant change at the end of study. Conclusion: It is to be concluded that patient counselling based intervention using PIL improved blood pressure and medication adherence in hypertensive patients. The intervention was helpful in enhancing knowledge and creating awareness regarding disease and medication.
Keywords: Hypertension; Pharmacist intervention; Medication adherence; Blood pressure; Hypertension related knowledge